PENGEMBANGAN ADOBE FLASH BERBASIS POWER POINT PADA MATERI PENCERNAAN MANUSIA - abdul rohman (Universitas Muhammadiyah Purwokerto, 2022)
The purpose of this is study (1) find to out the analysis of the needs of adobe flash based power point media; (2) describe to the form of power point-based adobe flash media; (3) to find out the level of validity of adobe flash based on power point. Research method is research and development (R&D) with research subjects as teachers in Madrasah Ibtidaiyyah Qamarul Huda Banaran. The results of the study are as follows: (1) the real condition of the use of learning media currently obtained from questionnaires and interviews that indicate the level of science learning media needs; (2) form of development of adobe flash media containing human digestive material which is implemented in the application of images and videos; (3) the average score obtained was 76% while the validation test based on the media expert validation sheet obtained an average of 78%; ( 4) individual trials obtained an average of 4.52, a mean group test of 4.49 and a limited group trial obtained a mean of 4.51. From these results it can be concluded that the adobe flash media is feasible to use; (5) effectiveness test on adobe flash media with a t test value of 34.820.